Living cumulative network meta-analysis to reduce waste in research: A paradigmatic shift for systematic reviews?. Issue 1 (December 2016) - Vandvik, Per; Brignardello-Petersen, Romina; Guyatt, Gordon
Abstract In a recent research article inBMC Medicine, Créquit and colleagues demonstrate how published systematic reviews in lung cancer provide a fragmented, out-of-date picture of the evidence for all treatments. The results and conclusions drawn from this study, based on cumulative network meta-analyses (NMA) of evidence from randomized clinical trials over time, are quite compelling. The inherent waste of research resulting from incomplete evidence synthesis has wide-reaching implications for a range of target groups including developers of systematic reviews and guidelines and their end-users, health care professionals and patients at the point of care. Building on emerging concepts for living systematic reviews and NMA, the authors propose "living cumulative NMA" as a potential solution and paradigmatic shift. Here we describe how recent innovations within authoring, dissemination, and updating of systematic reviews and trustworthy guidelines may greatly facilitate the production of living NMA. Some additional challenges need to be solved for NMA in general, and for living cumulative NMA in particular, before a paradigmatic shift for systematic reviews can become reality. Please see related research article:https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-016-0555-0